EVALUATION OF ANTIOXIDANT ACTIVITY OF HOMONOIA RIPARIA LOUR., KIRGANELIA RETICULATA (POIR) BAILL., PHYLLANTHUS FRATERNUS WEBSTER AND PEDILANTHUS TITHYMALOIDES (LINN.) POIT. AND ITS CORRELATION WITH THE TOTAL PHENOLIC AND FLAVONOID CONTENTS. - UJWALA C. BAPAT,; DEEPALI R. MHAPSEKAR, (International Journal of Pharma and Bio Sciences, 2015)
Plants of Euphorbiaceae are used to cure various diseases in traditional systems of medicine. For present study, Homonoia riparia, Kirganelia reticulata, Phyllanthus fraternus and Pedilanthus tithymaloides were selected on the basis of their availability and antimicrobial activity. Plant phenolics and flavonoids are known to possess antioxidant activity. Hence, it was decided to evaluate the antioxidant activity of these extracts and correlate it with the total phenolic and flavonoid contents of the same. The antioxidant activity and total phenol and flavonoid contents were determined by the standard methods. The results showed that the highest antioxidant activity and the total phenolic and flavonoid contents were observed in DMSO extract of P. fraternus. There was a positive correlation between the total antioxidant capacity and total phenolic and flavonoid contents in all the extracts. The IC50 values obtained indicated maximum antioxidant potential in the extract of male flowers of H. riparia.